(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Despite the fact that water covers 71% of the land surface, water is a limited natural resource. Fresh water makes up approximately 2.5 percent of total water on the planet, and it is used for a variety of reasons including household, irrigation, and industrial. Due to haphazard population expansion, frequent droughts, and changing climate patterns, water shortage has become a major worldwide issue. In a developing country like India, which has a long history of rural culture, the need for household water is fast increasing. The practicality of roof rain water collection in a Pirwadi hamlet in Kolhapur district (MS), India, was investigated using geospatial tools. Using a Google picture of the research location, global mapper, and Arc Gis ver. nine point three software, the various types of roof areas of dwellings and buildings in the hamlet were discovered and computed. The Gould and Nissen formula and Rande’s coefficient of runoff index for various types of roofs were used to determine the potential of roof rain water collecting (1999). The whole potential of roof rain water collection, according to the research, is estimated to be 11457490.78 Lt., which is more than enough to cover the village’s full annual drinking and cooking demands. In rural areas, rainwater collection systems are particularly helpful in alleviating the problem of water scarcity.